The role of necrophagous infusorians, Colpoda, in the planktic community of the Black Sea coastal waters. - Pasternak, Anna F; Kopylov, A I (PANGAEA, 1983)
The life cycle of infusorians belonging to genus Colpoda, dormant cysts of which were found on planktic crustaceans of the Black Sea coastal waters, is described. Population strength of Colpoda is maximum in autumn. The infusorians had no harmful effect on their host. It has been noted that Colpoda enhances decomposition of dead animals.
(Table 1) Population density and infestation of Paracalanus parvus during the year in the Blue Bay, Black Sea
Keywords: Archive of Ocean Data; ARCOD; Black Sea; BlueBay; MULT; Paracalanus parvus; Percentage